Global Marketing Strategic Approaches on Multi National Companies Product Development - Kalogiannidis , Stavros; Melfou, Katerina; Papaevangelou , Olympia (International Journal of Scientific Research and Management (IJSRM), 2020)
When it comes to business prospects, all organizations try to implement effective marketing mix strategies to ensure consistent operations. While these strategic approaches help a business sustain product development procedures, it also inflicts a humongous impact on issues concerning product development and promotion. In terms of global marketing, most multinational companies and retail firms aim to implement sustainable marketing mix strategies to build and expand their products or services to grab a considerable portion of foreign market share. This not only helps them to generate the desired revenues but also helps a business to enhance its customer base in the target market. This in turn escalates the eminence of the organizational reputation in the host market. However, this paper aims to examine the implications of marketing mix strategies on the product development issues in MNCs and/or retail industries. Through extensive literature mining from previous studies, this paper focuses on analyzing the effect of the strategic approaches used by most marketing experts to mediate the issues of product development. It intends to explore and cast light on the judicious role of the marketing mix in obtaining a competitive edge in most MNCs/retail firms. In the process, it also covers the relationship between the four basic components of the marketing mix, the 4Ps. The paper highlights how the marketing mix can influence the intricacies pertaining to the development process of a product. The study has the potential to provide managers with manual assistance on how these marketing strategies should be implemented and expanded to ameliorate business performance.